Branding Mythology in Postmodern Culture Sampoerna Cigarette Advertising A-Mild version "Nanti juga lo Paham" - Sadono, Teguh Priyo; Amina, Nurtyasih Wibawanti Ratna (Journal of Ecohumanism, 2024)
Advertising is an important instrument in Marketing Communication to build a Product Image. However, with the Republic of Indonesia Law number 32 of 2002 concerning Broadcasting, article 46 prohibits the promotion of cigarettes by displaying their appearance. To get around this, Sampoerna A-Mild cigarettes broadcast advertisements in the "You'll Understand" version which has meaning and mythology requirements. What mythology is used in branding to show the ideology of building a strong image for A-Mild Cigarettes? Through a postmodern philosophical approach in popular culture, this research wants to dismantle the sole dominance of Modernity. Using Roland Barthes' textual analysis method, it was revealed that the advertisement gave a strong meaning that the Sampoerna A-Mild cigarette advertisement wanted to create a masculine, strong, glamorous image in communal culture, as a form of resistance to the dominance of single modernity.